Muscarinic receptor regulation of chronic pain-induced atrial fibrillation - Gong, Chao; Ding, Yu; Liang, Feng; Wu, Shuang; Tang, Xiruo; Ding, Hongzhang; Huang, Wenjing; Yu, Xiaotong; Zhou, Likun; Li, Jun; Liu, Shaowen (Frontiers in Cardiovascular Medicine, 2022)
Atrial fibrillation (AF), one of the most common arrhythmias, is associated with a chronic emotional disorder. Chronic pain represents a psychological instability condition related to cardiovascular diseases, but the mechanistic linkage connecting chronic pain to AF occurrence remains unknown. Wild-type C57BL/6J male mice were randomly divided into sham and chronic pain groups. Autonomic nerve remodeling was reflected by the increased atrial parasympathetic tension and muscarinic acetylcholine receptor M2 expression. AF susceptibility was assessed through transesophageal burst stimulation in combination with electrocardiogram recording and investigating AERP in Langendorff perfused hearts. Our results demonstrated the elevated protein expression of muscarinic acetylcholine receptor M2 in the atria of mice subjected to chronic pain stress. Moreover, chronic pain induced the increase of atrial PR interval, and atrial effective refractory periods as compared with the sham group, underlying the enhanced susceptibility of AF. Thus, the autonomic cholinergic nerve may mediate mice AF in the setting of chronic pain.